Comparative effective dose of ciprofol and propofol in suppressing cardiovascular responses to tracheal intubation - Min Liao; Xiao-Ru Wu; Jia-Ning Hu; Xing-Zhou Lin; Tang‑yuan‑meng Zhao; Hu Sun (Scientific Reports)
Abstract Ciprofol, a novel γ-aminobutyric acid receptor agonist, outperforms propofol with minimal cardiovascular effects, higher potency, reduced injection pain, and a broader safety margin. Despite these advantages, ciprofol’s clinical research is still emerging. This study compares the median effective dose (ED50) and adverse reactions of ciprofol and propofol, in conjunction with sufentanil, for suppressing cardiovascular responses during tracheal intubation. Fifty-three adult patients scheduled for tracheal intubation under general anesthesia were enrolled and randomly assigned to receive either ciprofol (Group C) or propofol (Group P), according to a random number table. Tracheal intubation was performed using a standardized laryngoscope and endotracheal tube. The Dixon’s up-and-down method was employed to determine the ED50 and 95% effective dose (ED95) of ciprofol and propofol in inhibiting cardiovascular responses during tracheal intubation. Based on the pilot study, the initial dose for ciprofol was set at 0.35 mg/kg (with a 0.01 mg/kg increment) and for propofol at 2.0 mg/kg (with a 0.1 mg/kg increment). Probit analysis was applied to derive dose-response curves, while adverse reactions were continuously monitored. A total of 54 participants were included, with 24 in group C (1 excluded) and 30 in group P. Probit analysis revealed that the ED50 of ciprofol for inhibiting cardiovascular responses to tracheal intubation were 0.326 mg/kg (95% CI 0.304–0.337 mg/kg), and for propofol, 1.541 mg/kg (95% CI 1.481–1.599 mg/kg). The heart rate in group P was significantly higher than the group C at 1 minute (p = 0.026) and 3 minutes (p = 0.016) post-intubation. Systolic and diastolic blood pressures (SBP and DBP) decreased significantly before and after intubation compared to baseline values in both groups (p< 0.05). Group C experienced significantly less injection pain (p = 0.001), although the incidence of other adverse effects was not statistically different between groups (p > 0.05). Clinical Trial Registration: hppts://ClinicalTrials.gov; Identifier: NCT06095570(18/10/2023).